A rare case of spontaneous splenic rupture complicated by hemophilia A - Mahan, Mark E (J Surg Case Rep, 2019)
Splenic lymphangiomas are benign neoplasms resulting from congenital malformations of lymphatic channels manifesting as cystic lesions, occurring mostly in childhood. This process usually involves additional sites in a diffuse or multifocal fashion but although rare, can also present isolated to the spleen. The clinical picture varies from asymptomatic identified incidentally to nonspecific symptoms from compression of adjacent organs. Spontaneous rupture of these lesions can lead to hemoperitoneum, acute abdomen and hemorrhagic shock. We present the case of a 33-year-old male who required urgent exploration and splenectomy secondary to ruptured splenic lymphangioma, complicated by postoperative bleeding, re-exploration and blood transfusion from unknown Hemophilia A. Overall, it is important to be cognizant of this condition in the setting of left upper quadrant pain, even in an adult, as any delay in diagnosis or treatment can lead to life-threatening complication.